Urban Renewal after the Berlin Wall - Gabriel Ahlfeldt; Wolfgang Maennig; Felix J. Richter (Center for Economic Studies and ifo Institute (CESifo), 2013)
Urban renewal areas are popular but empirically understudied spatial planning instruments designed to prevent urban decline and induce renewal. We use a quasi-experimental research design to study the effects of 22 renewal areas implemented in Berlin, Germany, to increase housing and living quality in the aftermath of the city's division during the Cold War period. Our results suggest that the policy has helped reduce (increase) the number of buildings in poor (good) condition by 25% (10%). Property prices increased at an annual rate of 0.4-1.7% according to our preferred estimates. Evidence is weak at best, however, for positive housing externalities. More generally, our findings indicate that the efficiency of program evaluations for place based -policies using quasi-experimental methods increases with the number of targeted areas and areas that provide the counterfactual.
Keywords: D62; H23; R21; R31; 330; urban; renewal; revitalization; redevelopment; hedonic regression; quasi-experiment